2019
DOI: 10.1042/bsr20190667
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed circulating miRNAs in postmenopausal osteoporosis: a meta-analysis

Abstract: MicroRNAs (miRNAs) have been proven to play a crucial role in postmenopausal osteoporosis (PMO), and studies on their diagnostic value have been increasing. In our study, we aim to identify the key miRNAs in the PMO that might be potential biomarkers. A comprehensive systematic literature search was conducted by searching PubMed, Web of Science, Embase and Cochrane Library databases. In the total of 16 independent miRNA expression studies which contained 327 PMO patients and 328 postmenopausal (PM) healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Prior to this, studies have suggested aberrant expressions of miRs as an inevitable feature of various disorders which include osteoporosis, also miRs are important diagnostic biomarkers in osteoporosis. 15 Looking into the earlier studies involved the profiling of miRNAs in osteoporosis, we evidenced miR-125b as a dysregulated miRNA in the 3 databases which we screened and the expression levels of miR-125b in postmenopausal subjects confirmed these results.We first assessed the function of miR-125b in MC3T3-E1 cells, the outcomes indicated that miR-125b inhibited the cell viability and promoted the release of lactate dehydrogenase. The in vivo experiments in rats suggested that miR-125b decreased the bone mineral density and other biomechanical features of femur bones in rats.…”
Section: Discussionsupporting
confidence: 62%
“…Prior to this, studies have suggested aberrant expressions of miRs as an inevitable feature of various disorders which include osteoporosis, also miRs are important diagnostic biomarkers in osteoporosis. 15 Looking into the earlier studies involved the profiling of miRNAs in osteoporosis, we evidenced miR-125b as a dysregulated miRNA in the 3 databases which we screened and the expression levels of miR-125b in postmenopausal subjects confirmed these results.We first assessed the function of miR-125b in MC3T3-E1 cells, the outcomes indicated that miR-125b inhibited the cell viability and promoted the release of lactate dehydrogenase. The in vivo experiments in rats suggested that miR-125b decreased the bone mineral density and other biomechanical features of femur bones in rats.…”
Section: Discussionsupporting
confidence: 62%
“…We close this chapter by reporting the results of a meta-analysis carried out by Pala E et al [57]. The inclusion criteria established for the selection of studies considered only articles (n = 16) that evaluated c-miR levels in PM woF OP vs. PM woF CTRs.…”
Section: Pm Op Vs Prm Ctrsmentioning
confidence: 99%
“…Mandourah et al (2018) validated the up-regulation of miR-122-5p and miR-4516 in OP patients by RT-qPCR based on five subgroups of human blood sample control studies, i.e., non-OP controls, osteopenia without fracture, osteopenia with fracture, OP without fracture, OP without fracture. In another mate-analysis, samples collected from 327 PMO patients and 328 post-menopausal health samples were analyzed, and robust rank aggregation (RRA) was used to determine the up-regulation of miR-133a-3p in the blood of OP patients (Pala and Denkceken, 2019). Ma et al 2019verified that miR-181c-5p and miR-497-3p were down regulated in the blood of 86 post-menopausal women with OP or osteopenia, and increased after treatment with bisphosphonate and calcitriol, suggesting the role of diagnosis and treatment of OP.…”
Section: Overview Of the Collected Mirnasmentioning
confidence: 99%